2021
DOI: 10.1186/s13075-021-02446-6
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates as disease-modifying drugs in osteoarthritis preclinical studies: a systematic review from 2000 to 2020

Abstract: Bisphosphonates have been proposed as possible disease-modifying drugs in osteoarthritis. However, the evidence of their efficacy is poor and their outcomes presented a great heterogeneity. Therefore, the aim of this study is to systematically review the main effects of bisphosphonate use on synovial joint tissues and biochemical markers in preclinical studies over the past two decades (2000–2020). Three databases (Pubmed, Scopus, and Web of Science) were searched, and after screening, twenty-six studies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 59 publications
(84 reference statements)
0
22
1
1
Order By: Relevance
“… 17 , 104 In a recent systematic review including preclinical studies (n=26) over the past two decades (2000–2020), these drugs showed better chondroprotective effects at high doses with a dose-dependent manner as well as depending on the timing of treatment initiation in relation to OA stage (time-dependency). 105 Therefore, these agents may still be of potential benefits in certain OA endotypes with high rates of subchondral bone turnover. This phenotype-dependency has been demonstrated in pre-clinical research, where bisphosphonates are differentially effective in reducing pain and not only bone but also cartilage pathology in OA models with high versus low bone turnover.…”
Section: Bone-driven Endotypementioning
confidence: 99%
“… 17 , 104 In a recent systematic review including preclinical studies (n=26) over the past two decades (2000–2020), these drugs showed better chondroprotective effects at high doses with a dose-dependent manner as well as depending on the timing of treatment initiation in relation to OA stage (time-dependency). 105 Therefore, these agents may still be of potential benefits in certain OA endotypes with high rates of subchondral bone turnover. This phenotype-dependency has been demonstrated in pre-clinical research, where bisphosphonates are differentially effective in reducing pain and not only bone but also cartilage pathology in OA models with high versus low bone turnover.…”
Section: Bone-driven Endotypementioning
confidence: 99%
“…Subchondral bone lesions are visible in magnetic resonance imaging (MRI) in many patients with OA [ 68 ]. BPs delay and reverse pathological changes occurred in the bone and cartilage, and have a pain-relieving effect in animal model [ 69 ]. They can inhibit MMPs expression [ 70 ].…”
Section: Oa Treatmentmentioning
confidence: 99%
“…In addition to their main antiresorptive properties, BPs are believed to have antiinflammatory and analgesic effects [4,[44][45][46][47][48], which make them an attractive potential treatment for multiple diseases, including osteoarthritis (OA). Meta-analyses and systematic reviews have concluded that BP studies have controversial results, and BP effects may be more related to pain relief than disease modification [48][49][50]. These pain-relieving effects could be beneficial for some individuals, but in human or animal athletes, masking pain could also be dangerous and lead to further deterioration of joint conditions.…”
Section: Therapeutic Effects Of Bisphosphonatesmentioning
confidence: 99%